Evaluating the scripts and thresholds of general practitioners for diagnosing heart failure in elderly people - Decaluwe, Klaartje (BMC Fam Pract, 2016)
BACKGROUND: Multiple diagnostic algorithms for heart failure exist. However, it is unclear whether these algorithms are incorporated in the ‘scripts’ clinicians use in every day practice. Scripts are networks of organised knowledge that are acquired and accumulated during clinical training and are refined with each clinical encounter. This study was conducted to evaluate the scripts and thresholds that GPs use to diagnose heart failure in patients aged 75 years and older. METHODS: The scripts and thresholds of 130 Belgian GPs in training and 63 experienced trainers were compared using an online questionnaire based on the same principles as the script concordance test. Two major cases with an open question and 19 minor cases with closed questions were presented. For the minor cases, all of the respondents were asked to assign a diagnostic power to individual cues. Based on these powers, a diagnostic threshold was calculated for each respondent for the two major cases. RESULTS: The trainers and trainees used the same scripts to diagnose heart failure in the two major cases. Only ~50 % of the participants used natriuretic peptides in their scripts, although they judged it as the most powerful marker to demonstrate or exclude heart failure. The power that respondents gave to several cues differed significantly according to the context in which these cues were presented. In general, the average exclusive power of different cues was lower than the demonstrative power of the cues. There was no difference in diagnostic threshold between the trainers and trainees. CONCLUSION: Young, inexperienced GPs used the same scripts as older, more experienced GPs. In general, technical investigations were less frequently queried, compared to elements of the medical history and the clinical examination. The clinical context had a strong impact on the diagnostic power that was assigned to different factors. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12875-016-0481-4) contains supplementary material, which is available to authorized users.